PENGARUH SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERN TERHADAP KEPUASAN KARYAWAN DALAM PROSES PENGGAJIAN DENGAN KOMPETENSI SUMBER DAYA MANUSIA SEBAGAI VARIABEL MEDIASI - Fadhilah, Nur; Hariyono, Anwar (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2026)
The purpose of this study is to examine how Accounting Information Systems (AIS) and Internal Control Systems (ICS) impact employee satisfaction during the payroll process; at PT. Swabina Gatra, Human Resource Competence (HRC) is used as a mediating variable. Data collected from 55 workers were analyzed using SEM-PLS (SmartPLS 4). The results show that, although ICS does not have a significant effect on employee satisfaction directly, ICS also has a positive and significant effect on employee satisfaction and ICS. However, ICS also has a positive and significant effect on employee satisfaction and ICS, through the mediator role of ICS.